Challenges in Removing the Essure® Device - Daniëlle M. van Gastel; Liselotte W. Maassen; Carolien A. M. Koks; Sebastiaan Veersema; Marlies Y. Bongers (Case Reports in Obstetrics and Gynecology)
We present a case about Essure® removal surgery in which the third markers of the device have torn off. The woman needed a second surgery for complete removal of the devices. Fluoroscopy during surgery is a good method to visualize the lost fragments. With fluoroscopy, a hysterectomy is not needed for complete removal. It is important to understand the structure of the device and to be aware of the four radiopaque markers during surgery and their removal.